Customization contour line generated with conditional parameter using python and arcgis - Muhammad Akram, Mohamad A’sim (2023)
Topographic maps have been widely used in various fields such as recreational activities, engineering, construction, agriculture, and safety operations. With a lot of features included in topographic maps like contour lines, legends, waterbodies, and manmade structures, users may read and interpret the maps easily. This study will focus on determining, analysing, and proposing points and discontinued contour lines by a certain parameter (30 metres), including generating output that can be loaded in ArcGIS. ArcGIS and Python are used in this study to conduct data preparation and analysis. A contour lines map in shapefile format provided by MySpatial is used to complete this study.A few labelling processes are required to extract important attributes to be analysed in Python. To satisfy the objectives, distance between pairs of points is determined by using the Euclidean distance formula to determine the proposed points and discontinued contour line by certain parameters. As a result, a new customised contour line map was generated with the proposed new points that marked a significant gap between contour lines and discontinued contour lines. From 469 points, there are 154 points that are deleted after importing analysed data into ArcGIS. 32.84% points are deleted because of having distance less than defined parametres. There are only four additional points plotted on the new customised contour line map in total. When the distance between a pair of points exceeds the defined threshold, an additional point is proposed. The additional points on the map indicate that there is a significant gap between contour lines to generate new customised contour lines map. From the new customised contour lines map, farmers like the owner of an oil palm plantation can make data-driven decisions about constructing terraces, leading to increased revenue and profit.